what is a fused sentence?

A fused sentence, also called a run-on, occurs when a writer has connected two main clauses with no punctuation.

Question

Asked 8/27/2010 6:25:24 PM

Updated 2/16/2014 1:47:26 PM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

s

Rating

There are no new answers.

Solve: 4 - 9x = 29 - 4x **Weegy:** I'm sorry, i'm not good in math. (More)

Question

Expert Answered

Updated 2/26/2014 7:58:11 PM

1 Answer/Comment

4 - 9x = 29 - 4x

-9x + 4x = 29 - 4

-5x = 25

x = 25/-5

x = -5

-9x + 4x = 29 - 4

-5x = 25

x = 25/-5

x = -5

Added 2/26/2014 7:58:11 PM

This answer has been confirmed as correct and helpful.

Solve for x: 4 - 9x = 29 - 4x **Weegy:** 4 - 9x = 29 - 4x, -9x + 4x = 29 - 4,
-5x = 25,
x = 25/-5,
x = -5 **User:** Solve for x:
13 + 5x = 22 + 8x **Weegy:** 13 + 5x = 22 + 8x,
5x - 8x = 22 - 13,
-3x = 9,
x = 9/-3, x = -3 (More)

Question

Expert Answered

Updated 2/26/2014 8:00:08 PM

0 Answers/Comments

Solve for x: 13 + 5x = 22 + 8x
**Weegy:** x = 6/8 (More)

Question

Expert Answered

Updated 247 days ago|2/2/2024 2:29:12 PM

1 Answer/Comment

To solve for x, we want to isolate x on one side of the equation.

First, let's simplify the equation:

13 + 5x = 22 + 8x

We can start by subtracting 5x from both sides to move all the x terms to one side:

13 + 5x - 5x = 22 + 8x - 5x

13 = 22 + 3x

Next, we can subtract 22 from both sides to isolate 3x:

13 - 22 = 22 + 3x - 22

-9 = 3x

Finally, we divide both sides by 3 to solve for x:

-9 / 3 = 3x / 3

-3 = x

So the solution is x = -3

First, let's simplify the equation:

13 + 5x = 22 + 8x

We can start by subtracting 5x from both sides to move all the x terms to one side:

13 + 5x - 5x = 22 + 8x - 5x

13 = 22 + 3x

Next, we can subtract 22 from both sides to isolate 3x:

13 - 22 = 22 + 3x - 22

-9 = 3x

Finally, we divide both sides by 3 to solve for x:

-9 / 3 = 3x / 3

-3 = x

So the solution is x = -3

Added 247 days ago|2/2/2024 2:29:10 PM

This answer has been confirmed as correct and helpful.

Solve:
12x + 3 = 3x + 6 **Weegy:** Answer:
a=-5x/2 (More)

Question

Updated 7/16/2014 11:43:58 PM

1 Answer/Comment

12x + 3 = 3x + 6

12x - 3x = 6 - 3

9x = 3

x = 3/9 = 1/3

12x - 3x = 6 - 3

9x = 3

x = 3/9 = 1/3

Added 7/16/2014 11:43:58 PM

This answer has been confirmed as correct and helpful.

39,503,555

questions answered

There are no comments.